Aberrant formation of long-range projections across different neurodevelopmental disorders converges on molecular and cellular nexuses - Furlanetto, Federica; Martin Segura, Alejandro; Kravikass, Mathar; Dolai, Pritha; Frank, Sarah; Turan, Sören; Luna Leal, Angélica; Käseberg, Stephan; Schweiger, Susann; Lie, Dieter Chichung; Zaburdaev, Vasily; Karow-Falk, Marisa; et al. (2026)
Establishing long-range connections during human brain development is an intricate multi-step process disturbed in many neurodevelopmental disorders (NDDs). The aberrant formation of these connections is caused by mutations in a plethora of different genes with distinct molecular functions, triggering the question of whether there are common key downstream mediators at which different pathologies are converging. We employed brain organoids to model early human brain developmental aspects of Coffin-Siris-like 9, Opitz BBB/G, and Pitt-Hopkins syndromes. These NDDs are caused by mutations in SOX11, MID1, and TCF4 respectively, and are characterized by a multitude of distinct symptoms yet share alterations in long-range projections as a common feature. Here, we uncover that mutations in all three genes phenotypically converge, showing impaired neurite extension with increased tortuosity and decreased growth speed resulting in shorter beelines. Moreover, the mutant neurites exhibit a decrease in growth persistence providing a conceptual framework explaining why long- but not short-range connections are affected. Correlating with the converging cellular phenotype, molecular characterization revealed a striking convergence on signaling pathways implicated in the interaction of neurites with their extracellular environment. In-silico modeling and perturbation of neurite outgrowth suggest that altered neurite-extracellular environment interactions are sufficient to recapitulate the mutant phenotypes but also facilitate the prediction of specific parameters causing disturbed neurite growth in mutant neuron
https://cris.fau.de/converis/publicweb/Publication/354808213